Social Incubation in Pakistan: Enabling Student Mobilization During the COVID-19 Pandemic - Ehsan, Anam Noor; Noorali, Ali Aahil; Ahmed, Kaleem Sohail (Journal of the Pakistan Medical Association, 2022)
To the Editor: Developing countries, like Pakistan, with limited resources and budding health systems, face intense fear and despondency amongst the public, leading to worsening outcomes as wave after wave of the pandemic hits. (1) This helplessness is felt most by students and various health profession trainees who are the least vulnerable, yet the most underutilized. Combatting this frustration led to five medical students strategizing a mechanism to amass the country's collective resilience, expertise, and knowledge. This endeavor has since grown from March 2020 into an international autonomous taskforce of 700+ volunteers: The Student Taskforce Against COVID-19, an assortment of ten distinct COVID related efforts. (2,3) As we transitioned from a social incubator to a need-of-the-hour platform, our experiences taught us that five key values were central to enabling trainee led reform: a) strong leadership amongst working groups, b) strategic innovation targeted at developing real-time solutions to emerging and existing healthcare problems, c) reliable communication of authentic and relevant information in the midst of rumor and misinformation overload, d) community support and partnerships on individual and regional levels, and e) multidisciplinary teamwork amongst diverse volunteer groups. (Read more about us at: http://www.stac19.org/). Our initiatives relied on synergism between backgrounds in allied health, engineering, media, marketing, and entrepreneurship. The diversely skilled volunteers from across Pakistan led efforts ranging from telehealth programmes focusing on national critical care support and virtual mental health counselling, to training and informational programs for staff and residents at senior citizen homes and for the general public via a centralized student-manned helpline. The approach to these programmes was founded on the balance between functionality and sustainability with stakeholder involvement integrated at every tier. Although our experiences in Pakistan did face educational and economic limitations, they were very similar to patterns of student involvement in combating this crisis globally. (4) What this initiative has shown is that the interplay between diversity, synergism and collaboration is the key foundation for large-scale impact. This model of student mobilization can be reproduced in other crisis settings beyond the pandemic, beyond healthcare settings and beyond socioeconomic barriers. Continuous...